HUBUNGAN ANTARA FAKTOR INDIVIDU DAN BEBAN KERJA MENTAL DENGAN KELUHAN KELELAHAN KERJA PADA PENGEMUDI HAUL DUMPTRUCK: The Correlation Between Individual Factors and Mental Workload with Fatigue Complaints on Haul Dumptruck Driver - Faris Mohamad Minarna; Indriati Paskarini (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2018)
Haul dumptruck is a heavy-duty vehicles which is used to haul the overburden from loading point to disposal area. Haul dumptruck is driven by operators who have a high enough workload risk, especially on mental activity. The purpose of this study was to learn the correlation between mental workload with fatigue complaints of PT. MKP haul dumptruck operators at PKP2B PT. Mandiri Intiperkasa Site Krassi, Tarakan, Kalimantan Utara. This research was an analytic observational research with cross sectional design. The Sample of this research was 110 PT. MKP haul dumptruck operators at PKP2B PT. Mandiri Intiperkasa Site Krassi. The Variables of this research were individual factors (age, gender, and years of service), mental workload, and fatigue complaints. The data were analyzed by spearman correlation test to analyze the correlation between variables. The results showed 50% of haul dumptruck operators were 35-44 years old, 100% male, and 32.7% had 7-10 years of service. Most of haul dumptruck operators (58.2%) had very high mental workload levels and 68.2% was having low-grade fatigue complaints. The significant Ï value of the spearman test between mental workload and fatigue complaints was 0,400, while the correlation coefficient value was -0,081. The conclusion of this reasearch indicated that there was not a significant correlation between mental workload and fatigue complaints on haul dumptruck operators. Recommendation for the company are forming a labor unions, fixing cottage rest areas, giving co-worker when haul dumptruck operators complain of fatigue and mental workload on high level, and maintainin-developing a fatigue management as well as raising workers' awareness on its application.